Analisis Motivasi Wisatawan Terhadap Keputusan Berkunjung di Desa Wisata Lamajang - Syawaluddin Lingga; Zia Kemala (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2022)
Analysis of Tourist Motivation on the Decision to Visit in the Lamajang Tourism Village was a study conducted to see the effect of tourist motivation to increase visiting decisions. If there was an influence in the decision to visit, then the motivation of tourists provided an increase in the decision to visit. But, if there is no influence in the decision to visit, then the motivation of tourists does not provide an increase in the decision to visit. The research method used was a quantitative research method with descriptive analysis with verification approach. Data collection techniques were observations, interviews, and questionnaires. Primary data sources were obtained from a questionnaire of 110 respondents. The results showed that the variable Tourist Motivation influenced which decision to visit. It can be seen from the increase of Tourist Motivation can provide an increase in Visiting Decisions. In addition, Tourist Motivation was also influenced the Visiting Decision. Based on the results of the Determination Coefficient Test showed that the variable Tourist Motivation gave effect as much as 31,2% and the remaining 68,8% is influenced by other factors were not examined in this study. Based on these results it can be concluded that Tourist Motivation had had an influence in improving the Visiting Decision.